Method of fabricating glass via filled with tin-based intermetallic compound and substrate

CN122935262APending Publication Date: 2026-10-16XIAMEN SKY SEMICON TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202610963784.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-06-30
Publication Date
2026-10-16

AI Technical Summary

Technical Problem

然而传统Cu电镀填充存在明显的局限性:在面对高深宽比的TGV时极其容易产生空洞缺陷;且填充速度缓慢,往往需要数小时才能完成单批次填充,导致制造成本居高不下

Benefits of technology

本申请提供了一种基于锡基间金属化合物填充的玻璃通孔制备方法和基板,巧妙地结合了化镀工艺的高共形性与锡膏毛细填充的高效性。通过在玻璃孔壁预制化镀铜层并进行等离子体表面改性,为液态金属提供了极佳的润湿界面;辅以外力打破深孔阻力,彻底替代了传统大深宽比玻璃通孔极其依赖的“PVD沉积+长时间电镀填孔”路线。该方案实现了深宽比大于10:1微孔的秒级致密填充,将缺陷成本从高昂的报废降维至可控返修,赋予了封装基板更优异的可靠性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122935262A_ABST
    Figure CN122935262A_ABST
Patent Text Reader

Abstract

The application discloses a kind of based on tin-based intermetallic compound filling glass via preparation method and substrate, the method comprises: providing glass substrate with via;Forming copper plating layer on the surface of substrate and the inner wall of via;Surface modification treatment is carried out to copper plating layer to adjust interface energy;Tin paste is printed on the surface of substrate;Tin paste is melted by heating, and under the assistance of external force, liquid tin paste is filled into via by the combined driving of external force and capillary force;Finally, reflow treatment is carried out to form dense tin-based intermetallic compound.The application cooperates surface modification with conformal copper plating layer, combines the capillary filling mechanism of external force assistance, completely replaces the traditional time-consuming and easy to produce hollow electroplating copper filling process, realizes the efficient, low cost, non-hollow filling of large aspect ratio via.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of semiconductor chips, and in particular to a method for fabricating glass vias and a substrate based on tin-based intermetallic compounds. Background Technology

[0002] Through-Glass Vias (TGV) are showing a clear trend toward commercialization in 3D integrated microsystems. Against the backdrop of surging computing power demands from AI and high-performance computing chips, the industry urgently needs to develop low-cost, void-free, high electrical performance, and high thermal reliability TGV filling processes.

[0003] Currently, traditional TGV (Through-Vacuum Glass) filling processes largely rely on copper electroplating. However, traditional Cu electroplating has significant limitations: it is extremely prone to void defects when dealing with high aspect ratio TGVs; and the filling speed is slow, often requiring several hours to complete a single batch, resulting in high manufacturing costs. Furthermore, some existing improvements rely on pre-depositing bonding layers such as titanium and tantalum, and wetting layers such as gold and copper on the via walls to facilitate the inflow of liquid metal. This process is not only cumbersome and costly, but the compatibility of dissimilar materials is also susceptible to fluctuations. Therefore, developing a high aspect ratio glass via filling technology that eliminates the need for complex interfacial vapor deposition layers and combines high filling efficiency with high thermomechanical reliability is a critical technological bottleneck that urgently needs to be addressed in the advanced packaging field. Summary of the Invention

[0004] To address the aforementioned technical problems in the prior art, this application proposes a method for fabricating glass vias based on tin-based intermetallic compounds and a substrate, thereby solving the aforementioned technical problems.

[0005] According to a first aspect of the present invention, a method for preparing glass vias based on tin-based intermetallic compounds is provided, comprising the following steps: S1. Provide a glass substrate with several through holes; S2. A copper plating layer is formed on the surface of the glass substrate and the inner wall of the through hole; S3. Perform surface modification treatment on the copper plating layer covering the inner wall of the through hole to adjust the interfacial energy of the copper plating layer. S4. Print solder paste on the surface of the glass substrate so that the solder paste covers the opening of the through hole; S5. The glass substrate is heated to melt the solder paste into a liquid state, and under the applied external force, the liquid solder paste is driven to fill the through-hole along the copper plating layer on the inner wall of the through-hole through the combined action of external force and capillary force; and S6. The liquid solder paste filling the through holes is reflowed to solidify the liquid solder paste and form a tin-based intermetallic compound.

[0006] This application combines surface modification (adjusting interfacial energy) with a combined driving mechanism of "capillary force + external force" to successfully overcome the flow resistance of liquid in through-holes with large aspect ratios. This method eliminates the time-consuming traditional electroplating copper process and the complex physical deposition of metal barrier / wetting layers, significantly improving filling efficiency and reducing costs, and fundamentally avoiding the generation of electroplating voids.

[0007] In one possible implementation, the surface modification treatment is plasma treatment; after surface modification, the contact angle between the liquid solder paste and the copper plating layer on the inner wall of the via is 0° to 30°. This setup can precisely, uniformly, and without residue adjust the inner wall of the glass to a hydrophilic state with a contact angle of 0° to 30°, which provides a stable and sufficient positive capillary pull for the liquid solder paste, ensuring excellent spreadability of the solder paste on the glass surface.

[0008] In one possible implementation, S5, under the condition of applying external force, also includes applying ultrasonic vibration to the glass substrate, or establishing a pressure difference across the via for pressure filling. Introducing ultrasonic vibration can effectively break up and expel tiny air bubbles generated during the filling process using the acoustic cavitation effect, completely eliminating the risk of voids; introducing a pressure difference (positive or negative pressure) across the via can provide driving force, working in conjunction with capillary force to solve the problem of fluid stagnation at extremely high aspect ratios.

[0009] In one possible implementation, the capillary force driving the liquid solder paste within the via satisfies the following formula: ,in, For capillary rise height, The surface tension coefficient of liquid solder paste. Contact angle, Let ρ be the density of the liquid solder paste, g be the acceleration due to gravity, and r be the radius of the via. This formula provides reliable theoretical and computational support for subsequent adjustments to process parameters.

[0010] In one possible implementation, the process temperature for heating the glass substrate in S5 is controlled between 25°C and 80°C, and the surface tension coefficient of the liquid solder paste is... The surface tension of the liquid solder paste ranges from 20 mN / m to 40 mN / m. By precisely locking the heating process temperature within the range of 25°C to 80°C, the surface tension of the liquid solder paste can be accurately adjusted and maintained between 20 mN / m and 40 mN / m. Excessive temperature causes a sharp drop in tension, thus weakening the capillary effect; this temperature window ensures optimal capillary traction performance.

[0011] In one possible implementation, the via has an aspect ratio greater than 10:1 and a diameter of 5 μm to 50 μm. This configuration highlights the unique solution capability of this invention in demanding packaging scenarios such as micro-aperture and deep 3D interconnects.

[0012] In one possible implementation, during the liquid solder paste filling of vias, an online monitoring system acquires the process state parameters within the vias and adjusts the plasma treatment parameters or the magnitude of the external force based on these parameters. This online monitoring system dynamically adjusts the process state, effectively addressing the capillary effect inconsistencies caused by minor environmental fluctuations or material differences in mass production, significantly improving the consistency and yield of mass production on actual production lines.

[0013] In one possible implementation, the glass substrate is made of BF33 glass. BF33 glass exhibits excellent thermal compatibility with this process.

[0014] According to a second aspect of the present invention, a substrate is provided, which is prepared by the above-described preparation method: the substrate includes a glass substrate and a through-hole penetrating the glass substrate, the inner wall of the through-hole and the surface of the glass substrate are conformally covered with a copper plating layer; the space within the through-hole surrounded by the copper plating layer is densely filled with a tin-based intermetallic compound; the outer peripheral surface of the tin-based intermetallic compound is tightly bonded to the copper plating layer.

[0015] In one possible implementation, the aspect ratio of the through hole is greater than 10:1.

[0016] The method and structure provided by this invention have the following beneficial effects: This application provides a method and substrate for fabricating glass vias based on tin-based intermetallic compounds, ingeniously combining the high conformality of electroless plating with the high efficiency of tin paste capillary filling. By pre-plating a copper layer on the glass via wall and performing plasma surface modification, an excellent wetting interface is provided for the liquid metal; furthermore, external force is used to overcome the resistance of deep holes, completely replacing the traditional "PVD deposition + long-term electroplating filling" route that is heavily reliant on large aspect ratio glass vias. This solution achieves second-level dense filling of microholes with an aspect ratio greater than 10:1, reducing defect costs from high scrap rates to controllable rework, and giving the packaging substrate superior reliability. Attached Figure Description

[0017] The accompanying drawings are included to provide a further understanding of the embodiments and are incorporated in and constitute a part of this specification. The drawings illustrate embodiments and, together with the description, serve to explain the principles of the invention. Other embodiments and many anticipated advantages of the embodiments will be readily recognized as they become better understood through reference to the following detailed description. Elements in the drawings are not necessarily to scale. The same reference numerals refer to corresponding similar parts.

[0018] Figures 1a-1e This is a flowchart of a traditional glass through-hole preparation method in the prior art; Figures 2a-2fThis is a flowchart of a glass via fabrication method based on tin-based intermetallic compound filling, according to an embodiment of the present invention.

[0019] Explanation of reference numerals: In prior art drawings, 101-glass substrate, 102-through hole, 103-bonding layer, 104-electroplated metal layer, 105-metal conductive pillar; In the drawings of embodiments of this application, 201-glass substrate, 202-through hole, 203-plated copper layer, 204-solder paste, 205-tin-based intermetallic compound. Detailed Implementation

[0020] The present application will now be described in further detail with reference to the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are merely illustrative of the invention and not intended to limit it. Furthermore, it should be noted that, for ease of description, only the parts relevant to the invention are shown in the accompanying drawings.

[0021] It should be noted that, unless otherwise specified, the embodiments and features described in this application can be combined with each other. This application will now be described in detail with reference to the accompanying drawings and embodiments.

[0022] Figures 1a-1e This is a flowchart of a traditional glass through-hole preparation method in the prior art, such as... Figure 1a As shown, the traditional glass through-hole fabrication process first provides a complete piece of BF33 glass as the glass substrate 101. Subsequently, as... Figure 1b As shown, the glass substrate 101 is processed using a laser-induced etching process to form multiple through holes 102 penetrating the upper and lower surfaces. Next, as... Figure 1c As shown, a bonding layer 103 is uniformly deposited on the upper and lower surfaces of the glass substrate 101 and the inner sidewall of the through-hole 102 using a physical vapor deposition (PVD) process. Based on this, as... Figure 1d The electroplating process is shown, reducing the metal on the bonding layer 103 to form an electroplated metal layer 104 of a certain thickness. This electroplated metal layer 104 not only completely fills the interior of the through-hole 102 but also covers the upper and lower surfaces of the glass substrate 101. Finally, as shown... Figure 1e As shown, the processes of resist removal, etching, and chemical mechanical planarization (CMP) are performed sequentially. Through these processes, excess electroplated metal layers 104 on the upper and lower surfaces of the glass substrate 101 and the bonding layer 103 at the bottom are completely removed until the original surface of the glass substrate 101 is exposed. At this point, the metal material is only trapped inside the through-hole 102, forming the final independent metal conductive pillar 105, thereby completing the metallized electrical interconnection structure of the conventional glass through-hole.

[0023] The aforementioned traditional electroplating copper-filling process has significant limitations in practical applications. When dealing with high aspect ratio glass vias, this electroplating process is highly prone to creating voids within the vias, severely impacting the overall electrical performance and thermomechanical reliability of the interconnect structure. Furthermore, the electroplating filling speed is extremely slow, often requiring several hours to complete a single batch, resulting in extremely low production efficiency. In addition, due to the cumbersome process steps and high dependence on expensive processing equipment (such as PVD and CMP equipment), the overall manufacturing cost of this traditional process remains high, making it difficult to meet the current demands of advanced packaging for low cost, high reliability, and large-scale mass production.

[0024] Figures 2a-2f This is a flowchart of a method for preparing glass vias based on tin-based intermetallic compounds according to an embodiment of the present invention, as shown below. Figure 2a As shown, the glass via fabrication method based on tin-based intermetallic compound filling of the present invention first provides a complete BF33 glass as a glass substrate 201. BF33 glass possesses excellent thermal and mechanical properties, meeting the stringent requirements of AI and high-performance computing chips for packaging substrates. Subsequently, as... Figure 2b As shown, the glass substrate 201 is precisely processed using specific techniques such as laser-induced etching to drill multiple through-holes 202 that penetrate the upper and lower surfaces of the substrate. To meet the requirements of ultra-high density three-dimensional interconnection in advanced packaging, the diameter of the through-holes 202 is strictly controlled within the range of 5μm to 50μm, and their aspect ratio is often greater than 10:1.

[0025] like Figure 2c As shown, a copper plating layer 203 is prepared on the upper and lower surfaces of the glass substrate 201 with through-holes 202 and on the inner wall of the through-holes 202 to provide a good conductive and adhesive foundation for subsequent liquid metal filling. Addressing the technical challenge of unstable contact angles due to the surface energy difference between dissimilar materials (glass and metal), this process introduces surface modification methods such as plasma treatment at or before / after this stage to modify the hole wall interface. By adjusting the interface energy, the contact angle θ between the subsequent liquid solder paste and the inner wall of the through-hole is precisely controlled within the ideal hydrophilic range of 0° to 30°, thus providing an excellent foundation for interfacial contact and positive capillary wetting.

[0026] After this surface treatment is completed, such as Figure 2d As shown, solder paste 204 is precisely coated onto the surface of the glass substrate 201 using processes such as stencil printing, so that the semi-solid solder paste 204 fully covers the openings of each through-hole 202. In this printing and subsequent filling processes, the process line can be equipped with an online monitoring system to acquire and dynamically adjust the process status parameters within the through-holes in real time, so as to overcome process fluctuations and ensure a high degree of consistency in the filling of the entire board during mass production.

[0027] like Figure 2e As shown, a glass substrate 201 coated with solder paste 204 is subjected to heat treatment. As the process temperature increases and is precisely controlled between 25°C and 80°C, the surface tension coefficient of the liquid solution... It is regulated and maintained within the range of 20 mN / m to 40 mN / m. The solder paste 204 melts and transforms into a liquid state. Driven by the strong capillary effect generated by the interaction of surface tension and adhesion, its rising or falling dynamics follow the formula: , Let ρ be the density of the liquid solder paste, g be the acceleration due to gravity, and r be the radius of the via. Specifically, facing the challenge of aspect ratios greater than 10:1, since capillary action alone may not be sufficient to completely fill the via, this process simultaneously applies external forces—for example, applying ultrasonic vibration to the glass substrate to break up and expel micro-bubbles, or establishing a pressure difference across the via for pressure filling. Driven by the synergistic effect of capillary force and external force, the liquid solder paste flows rapidly downwards along the via wall with extremely high board-wide processing efficiency, thus fully, completely, and without dead zones filling the entire via 202.

[0028] like Figure 2f As shown, a reflow process is used to perform overall heat treatment on the substrate, causing the liquid solder paste filling the vias 202 to undergo a complete phase change and solidify, reacting inside the vias to form a dense tin-based intermetallic compound 205. At this point, the glass vias are completely filled, and the end faces are flush with the electroless copper plating layer 203. This process completely avoids the defects of voids easily generated by traditional electroplated copper. Combined with SPI, AOI, and X-ray inspection, it can achieve extremely high average yield, ultimately producing a glass via interconnect structure with low cost, high filling efficiency, lower thermal stress, and higher thermal stability and conductivity, greatly improving the thermomechanical reliability of 3D integrated microsystems.

[0029] To further clarify the control conditions and synergistic mechanisms of each process step in the embodiments of this application, the following table details the key parameters and their preferred control ranges in the process of this application.

[0030] ; During the surface modification stage, plasma treatment is used to reduce the contact angle of the inner wall of the glass via. Strictly controlling the temperature within the range of 0° to 30° aims to significantly improve the wettability of dissimilar interfaces, providing sufficient initial positive capillary traction for the liquid solder paste. During the solder paste printing stage, Type 6 or finer particle size solder paste is preferred to precisely match the 5μm to 50μm micro-pore diameter, effectively preventing clogging at via openings. During the heat-filling stage, the process temperature is precisely limited to 25°C to 80°C, thereby controlling the surface tension of the liquid solder paste solution. The optimal hydrodynamic range is adjusted and maintained between 20 mN / m and 40 mN / m. Simultaneously, the applied external force is specifically quantified as an ultrasonic frequency of 20 kHz to 40 kHz or a pressure difference of 0.1 MPa to 0.5 MPa. Specifically, the recommended ultrasonic frequency for small-diameter pores is 40–60 kHz, and for large-diameter pores it is 15–20 kHz. The recommended pressure difference is 0.1–0.2 MPa for thin substrates, 0.3–0.5 MPa for thick substrates, and 0.2–0.3 MPa for multi-density pores. This specific intensity of external force effectively breaks the fluid stagnation within large aspect ratio (greater than 10:1) through-holes, overcoming the physical resistance of deep holes. Finally, during the reflow curing stage, by controlling the reflow peak temperature between 250°C and 280°C, sufficient thermodynamic phase transformation of the metal filling the holes is ensured, thereby forming a dense tin-based intermetallic compound (IMC). The combined effect of the parameter ranges in each of the above process stages fundamentally ensures the high efficiency, low cost, and void-free filling of high aspect ratio glass through-holes.

[0031] To illustrate the economic advantages of the process in industrial applications, the table below provides a detailed comparison of cost data between the process in this application and traditional copper electroplating processes.

[0032] ; The data in the table shows that the proposed process achieves significant cost reductions in the three core aspects of "personnel, machinery, and materials." Regarding labor costs, traditional electroplating production lines heavily rely on highly skilled personnel with electroplating expertise, while the proposed process only requires mid-level skilled personnel with basic SMT equipment operation skills. This significantly reduces annual labor costs and extends effective production time. In terms of equipment investment, the initial investment for a single traditional electroplating line is extremely high, and maintenance costs are substantial. The proposed process drastically reduces the initial investment per line, significantly shortens the investment payback period, and greatly reduces the company's fixed asset investment risk. Regarding consumables management, the proposed process eliminates the cumbersome process of monthly chemical replenishment and regular anode replacement required by traditional electroplating, resulting in higher material utilization and significantly optimized replacement frequency and management costs for consumables such as molds.

[0033] In addition to significant cost advantages, the process described in this application also demonstrates a leap forward in production efficiency that is unmatched by traditional electroplating. The specific efficiency advantage comparison data is shown in the table below.

[0034] ; This table comprehensively demonstrates the significant differences in processing time and throughput between the two processes. Traditional copper plating filling often takes more than ten hours per batch, with extremely long single-hole batch filling times. This application, however, fully utilizes liquid capillary effect and whole-board reflow technology to drastically reduce single-batch processing time to less than two hours, and single-hole filling time to an astonishingly low second level, achieving simultaneous filling of the entire board and completely breaking through the time bottleneck of traditional glass through-hole high aspect ratio filling. Thanks to this whole-board synchronous processing mechanism, the throughput per unit area of ​​this application's process has achieved a leapfrog increase, perfectly meeting the stringent requirements of the current advanced packaging field for large-scale, high-rate-of-use mass production.

[0035] In terms of finished product quality control and defect management, the process in this application also provides a higher tolerance for errors and a lower recovery cost. The specific yield and defect control advantages are compared in the table below.

[0036] ; The table shows that the average yield of this application's process has steadily improved compared to traditional copper plating processes. In terms of inspection, this application overcomes the limitation of traditional electroplating relying solely on X-ray internal sampling. It is perfectly compatible with SPI, AOI, and combined X-ray inspection, extending process monitoring from early solder paste printing volume and surface morphology to internal structure, achieving comprehensive quality control and effectively intercepting defects early in the process. More importantly, traditional copper plating, once defects such as voids or incomplete filling occur, is essentially impossible to repair due to process characteristics, resulting in high losses from direct scrapping. However, the process characteristics of this application mean that even if a small number of defects occur, the repair difficulty is extremely low; most can be resolved through routine manual repair, thus reducing defect costs from high scrap losses to controllable repair costs.

[0037] The present invention also provides a glass through-hole substrate with extremely high interconnect reliability. This substrate structure is prepared by the above-described preparation method, and its structure can be referred to as follows. Figure 2f The substrate is primarily composed of a BF33 glass substrate 201, on which are large aspect ratio through-holes 202 with a depth-to-width ratio greater than 10:1. The inner walls of the through-holes 202 and the surface of the glass substrate 201 are conformally covered with an electroless copper plating layer 203. Within the through-hole space surrounded by the electroless copper plating layer 203, a tin-based intermetallic compound 205, cured by reflow phase change, is densely and fully filled, and the outer periphery of the tin-based intermetallic compound 205 achieves excellent metallurgical bonding with the electroless copper plating layer 203. This composite electrical conductivity structure, with the electroless copper plating layer serving as the interface wetting and conductive network and the dense tin-based compound as the main filling core, not only completely eliminates the deep-hole void hazards of traditional pure electroplated copper structures but also significantly shortens the process time, giving the product excellent electrical conductivity and superior thermomechanical reliability.

[0038] The specific embodiments of this application have been described above, but the scope of protection of this application is not limited thereto. Any variations or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in this application should be included within the scope of protection of this application. Therefore, the scope of protection of this application should be determined by the scope of the claims.

[0039] In the description of this application, it should be understood that the terms "upper," "lower," "inner," "outer," etc., indicating orientation or positional relationships based on the orientation or positional relationships shown in the accompanying drawings, are used only for the convenience of describing this application and for simplification, and do not indicate or imply that the device or element referred to must have a specific orientation, or be constructed and operated in a specific orientation, and therefore should not be construed as a limitation of this application. The word "comprising" does not exclude the presence of elements or steps not listed in the claims. The word "a" or "an" preceding an element does not exclude the presence of a plurality of such elements. The simple fact that certain measures are recited in mutually different dependent claims does not indicate that combinations of these measures cannot be used for improvement. Any reference signs in the claims should not be construed as limiting the scope.

Claims

1. A method for preparing glass through-holes based on tin-based intermetallic compounds, characterized in that, Includes the following steps: S1. Provide a glass substrate with several through holes; S2. A copper plating layer is formed on the surface of the glass substrate and on the inner wall of the through hole; S3. Perform surface modification treatment on the copper plating layer covering the inner wall of the through hole to adjust the interfacial energy of the copper plating layer. S4. Print solder paste on the surface of the glass substrate so that the solder paste covers the opening of the through hole; S5. The glass substrate is heated to melt the solder paste into a liquid state, and under the applied external force, the liquid solder paste is driven to fill the through-hole along the copper plating layer on the inner wall of the through-hole through the combined action of the external force and capillary force; and S6. The liquid solder paste filled in the through hole is reflowed to solidify the liquid solder paste into a tin-based intermetallic compound.

2. The preparation method according to claim 1, characterized in that, The surface modification treatment is plasma treatment; after the surface modification treatment, the contact angle between the liquid solder paste and the copper plating layer on the inner wall of the through hole is 0° to 30°.

3. The preparation method according to claim 1, characterized in that, In step S5, under the condition of applying external force, the method further includes applying ultrasonic vibration to the glass substrate, or establishing a pressure difference at both ends of the through hole to perform pressure filling.

4. The preparation method according to claim 1, characterized in that, The capillary force driving the liquid solder paste within the through-hole satisfies the following formula: ,in, For capillary rise height, The surface tension coefficient of liquid solder paste. Contact angle, Let ρ be the density of the liquid solder paste, g be the acceleration due to gravity, and r be the radius of the via.

5. The preparation method according to claim 4, characterized in that, In step S5, the process temperature for heating the glass substrate is controlled between 25°C and 80°C, and the surface tension coefficient of the liquid solder paste is... It ranges from 20mN / m to 40mN / m.

6. The preparation method according to claim 1, characterized in that, The through hole has a depth-to-width ratio greater than 10:1, and the diameter of the through hole is between 5 μm and 50 μm.

7. The preparation method according to claim 2, characterized in that, During the process of filling the via with liquid solder paste, the process state parameters inside the via are acquired by an online monitoring system, and the parameters of the plasma treatment or the magnitude of the external force are adjusted based on the process state parameters.

8. The preparation method according to claim 1, characterized in that, The glass substrate is made of BF33 glass.

9. A substrate, characterized in that, The substrate is prepared by any one of claims 1 to 8: the substrate includes a glass substrate and a through hole penetrating the glass substrate, the inner wall of the through hole and the surface of the glass substrate are conformally covered with a copper plating layer; the space surrounded by the copper plating layer in the through hole is densely filled with a tin-based intermetallic compound; the outer peripheral surface of the tin-based intermetallic compound is tightly bonded to the copper plating layer.

10. The substrate according to claim 9, characterized in that, The aspect ratio of the through hole is greater than 10:1.